Peran Teknologi Informasi Media Digital Terhadap Motivasi Belajar Siswa Menurut Fahmi Taufiq Muhammad Maqbul - Juhairiyah, Juhairiyah; Muhlis, Achmad; Jannah, Faridatul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The purpose of this article is to examine the role of digital media information technology on student learning motivation through several research focuses 1). Types of Digital Media Technology in Schools to Increase Student Motivation. 2). The Influence of Digital Media Technology Users on Student Motivation Levels. 3). Challenges Faced by Students in Using Digital Media. The method used is literature by analyzing relevant literature. The results of this research confirm that the existence of information technology in the form of digital media can increase students' motivation to learn, students are becoming more active in increasing their knowledge, not only relying on the teacher's explanations in class, but students are active in searching for information themselves, creating work, with digital media it can make access easier. lessons, can encourage students to learn independently so that it can foster widespread student learning motivation. However, the use of digital media requires strict control so that it does not have a negative impact on students' creative development.